Hopes and Betrayals - Adeta, Matthew (Literamed Publications Nigeria Ltd, 2006)
Joke and Vincent, both born-again Christians,have been courting for years.The families of the couple are anxiously waiting for Joke to complete her National Youth Service Corps,so as to solemnize the couples marriage in the church.In the process, Joke meets Dele,the brother of her closest friend.Will Joke and Vincents relationship remain the same afterwards?
Keywords: Feelings; Fiction; Juvenile Literature; Love & Betrayal